2016
DOI: 10.1556/2060.103.2016.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia attenuates α1-adrenoceptor-mediated contraction in human varicose spermatic vein: The role of nitric oxide(Short communication)

Abstract: The effects of moderate hypothermia (28°C) on the response of human varicose spermatic vein to α 1 -adrenoceptor agonist phenylephrine and the role of endothelial nitric oxide (NO) in these effects were studied. Concentrationresponse curves for phenylephrine (10 −9 to 3 × 10 −4 M) were recorded in rings with and without endothelium at 37 and 28°C. To further analyze the role of NO, in the response to phenylephrine during hypothermia, the effects of this agonist in the presence of N G -nitro-L-arginine methyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The PI3K/Akt pathway is involved in endothelial NO production [6,7,22]. Similar to previous studies, the current study found that the PI3K inhibitor wortmannin (10 -7 M) abolished mild hypothermia-induced NO-mediated inhibition of phenylephrine-induced maximal contraction ( Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The PI3K/Akt pathway is involved in endothelial NO production [6,7,22]. Similar to previous studies, the current study found that the PI3K inhibitor wortmannin (10 -7 M) abolished mild hypothermia-induced NO-mediated inhibition of phenylephrine-induced maximal contraction ( Fig.…”
Section: Discussionsupporting
confidence: 89%
“…7A). As hypothermia causes decreased phenylephrineinduced contraction due to increase NO availability, this L-MANE-induced inhibition of eNOS phosphorylation resulting from combined treatment with phenylephrine and hypothermia seems to be associated with a L-NAME-induced decrease in NO production [4,5,22]. However, the L-NAME-induced increase in eNOS phosphorylation caused by phenylephrine alone at 37°C may be associated with compensatory eNOS activation due to competitive inhibition of L-NAME against L-arginine as a substrate of NO (supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia has been shown to induce significant changes in responsiveness of vascular smooth muscle cells to various drugs (6,7). Most of the previous studies examining the effect of hypothermia on smooth muscle responses have focused on the effects of cutaneous vessels (13,17,23) and information about non-cutaneous vessels is rather limited. Previously, we investigated the effects of hypothermia on diazoxide-(2) and cilostazol-induced (19) relaxations in calf cardiac vein and coronary artery.…”
Section: Introductionmentioning
confidence: 99%